2017
DOI: 10.1016/j.jct.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

High-temperature, high-pressure viscosities and densities of toluene

Abstract: I thank Professor Mark A. M c Hugh for his guidance throughout my undergraduate and graduate education. Dr. M c Hugh's guidance has truly been a significant factor in my growing love for the field of chemical engineering. Lastly, I would like to note that Dr. M c Hugh has never failed to keep me entertained and inspired through his lectures. It has been a pleasure working with Dr. M c Hugh. I would also like to thank Dr. Reddy Mallepally for working closely with me and teaching me how to perform high-pressure … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(25 citation statements)
references
References 65 publications
1
23
1
Order By: Relevance
“…HMN viscosity data from the present study are fit to a modified Tait equation for facile interpolation and ease of comparison to available literature data. The fitting procedure is described by Caudwell et al 3 and in our previous studies 13,39 and further details are found in the Note that the data of Cannet et al 31 , Barrohou et al 63 , Et-Tahir et al 32 , and Zeberg-Mikkelsen et al 63 deviate from those in the present study by as much as 11% at the lowest temperatures and highest pressures. A possible cause for these high deviations could be related to the fluid used to calibrate the falling-body viscometers used in each of these studies.…”
Section: Comparison To Viscosity Literature Data For Hmnsupporting
confidence: 52%
See 2 more Smart Citations
“…HMN viscosity data from the present study are fit to a modified Tait equation for facile interpolation and ease of comparison to available literature data. The fitting procedure is described by Caudwell et al 3 and in our previous studies 13,39 and further details are found in the Note that the data of Cannet et al 31 , Barrohou et al 63 , Et-Tahir et al 32 , and Zeberg-Mikkelsen et al 63 deviate from those in the present study by as much as 11% at the lowest temperatures and highest pressures. A possible cause for these high deviations could be related to the fluid used to calibrate the falling-body viscometers used in each of these studies.…”
Section: Comparison To Viscosity Literature Data For Hmnsupporting
confidence: 52%
“…Tomida et al 16 and Paredes et al 11 demonstrate that the pressure effect on K can be minimized and/or neglected when the ball rolls through a tube inserted in the body of the viscometer since the tube only experiences a very small differential pressure. Conversely, our previous studies 10,13 and the study of Sato et al 14 The final calibration equation for the RBVD utilized in our study is,…”
Section: Viscosity Calibrationmentioning
confidence: 82%
See 1 more Smart Citation
“…Viscosity sensing methods can be categorised into offline and online methods. Popular offline methods include capillary viscometry [7,8] and falling ball viscometry [9][10][11][12] . Although the offline methods are easy to apply, the measurement accuracy depends on manual operation.…”
Section: Introductionmentioning
confidence: 99%
“…Diesel and Jet FuelsCommercially available distillate fuels (e.g., diesel, gasoline, kerosene, jet fuels) are composed of hundreds of hydrocarbons. Composition depends on the source of the crude oil, distillation conditions, target fuel quality specifications[70,71], and additional processing and blending with additives.Table 8lists the limited number of experimental studies reporting the density of diesel and jet fuels up to HTHP conditions. Outcalt and colleagues[72, 73] measured the density of jet fuels JP-8 3773 (referred to as JP-8) and Jet A 4658 (referred to as Jet A) at high temperatures between 270 and 470 K and pressures up to 400 bar.…”
mentioning
confidence: 99%